Five Success Stages in Human Capital Planning Over LH Hotel Business - Lelly Cholilah Hasyim; Tantri Yanuar R Syah; Rhian Indradewa; Semerdanta Pusaka (Penerbit Kemala Indonesia, 2019)
The impact of globalization has made by business development in Indonesia. This condition have opportunities for entrepreneurs in industrial sectors to compete in attracting consumers. This condition is also caused by hospitality service industry to face intense competition and experience rapid growth and development. In addition, the competition formed spurred hospitality companies to further enhance their role in serving consumers. Based on the results, a market share survey by the LH Hotel consumers team only need clean, comfortable, and affordable rooms and good service. Consumers no longer need too many hotel facilities such as a variety of restaurants or rooms that are too large at high prices. Consumers are getting smarter in planning their trips so that there is a trend of hotels that have basic facilities needed by consumers but at low prices. The phenomenon and facts of the development of the hospitality business make the main foundation for LH Hotel in building a hospitality property that focuses on the needs of consumers for a 3-star hotel class. The hospitality industry that is cultivated by LH Hotel is a service industry that cannot be separated from the importance of managing human resources to be able to create maximum service quality. Therefore LH Hotel must implement a good human capital system in order to obtain and prepare competent human resources.